Effect of pipe elbow on flow pressures - Yang, Ge (2019)
This Final Year Project (FYP) report presents a study on the flow pressure loss in three pipe elbows made from same material and with different configurations. The purpose of this FYP is to improve the experimental result from the lab experiment “E2.6 Frictional Losses in Pipes and Fittings”, which is part of the core module “MA2071 Laboratory Experiments” for mechanical engineering undergraduate student in Nanyang Technological University (NTU) Three pipe elbows with different configurations were designed, fabricated and finally tested. The experiment procedure was strictly followed the procedure of “E2.6 Frictional Losses in Pipes and Fittings”. Based on the principle of “Fluid Mechanics”, the test result had met the expectation and therefore achieved the general purpose of this project, to provide a better understanding to the students on the effect of pipe elbow on flow pressures.